Risk factors associated with retinopathy of prematurity among neonates in a tertiary care hospital in Nepal - Shrestha, Jyoti Baba; Yadav, Reena; Shrestha, Jeevan Kumar; Shrestha, Laxman; Sah, Raman Prasad (Journal of Kathmandu Medical College, 2017)
Background: Retinopathy of prematurity is a vascular retinal disease that can cause blindness in premature new born babies. Several risk factors are associated with the incidence of ROP. Information and data on risk factors associated with ROP in context to Nepalese population is scarcely documented in literature. Objectives: The purpose of this study was to evaluate the risk factors of retinopathy of prematurity in premature infants admitted in the neonatal intensive care unit of Tribhuvan University Teaching Hospital. Methods: Neonates with gestational age of 36 weeks or less and birth weight of 2000 gram or less admitted to neonatal intensive care unit (NICU), during 2013 to 2015 were screened for retinopathy of prematurity. Risk factors and severity of retinopathy of prematurity were evaluated. The initial examination was carried out at 4-6 weeks after birth by indirect ophthalmoscope and retinopathy of prematurity positive and negative infants were compared subsequently. The Chisquare and independent t-tests were used for statistical analysis. A p value less than 0.05 was considered statistically signifi cant. Results: The incidence of retinopathy of prematurity was 22.6% and severe retinopathy of prematurity requiring treatment was observed in 3.2% of 93 neonates who had eye examinations. There was a signifi cant relationship between the occurrence of ROP and birth weight (p=0.000), gestational age (p=0.000), duration of oxygen therapy (p=0.009) and sepsis (p=0.002). However, insignifi cant relationship was observed between the occurrence of retinopathy of prematurity and gender, type of delivery, multiple gestation, premature rupture of foetal membrane, respiratory distress syndrome and hyperbilirubinaemia. Conclusion: The risk factors contributing to development of retinopathy of prematurity showed signifi cant relationship with immaturity, duration of oxygen supplementation and septicaemia. Journal of Kathmandu Medical College Vol. 5, No. 1, Issue 15, Jan.-Mar., 2016,page: 28-33